2023
DOI: 10.1007/s00217-023-04326-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-assisted extraction of cranberry seed oil: food waste valorization approach

Abstract: Cranberry pomace considered as a by-product of fruit industry contains seeds which may be processed to highly nutritive oil. Conventional extraction methods may be, however, harmful to natural environment, thus alternative, ultrasound-assisted extraction method may be useful tool to reduce environmental impact. In the following study, sonication was applied to extract oil from cranberry seeds. The aim of the study was to determine the most efficient conditions of ultrasound-assisted extraction of oil and to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The mechanisms of ultrasound-assisted extraction are based on fragmentation, erosion, sonoporation, and detexturation [38]. The mass transfer to the liquid phase is improved due to the collapse of cavitation bubbles, and moreover, this process is characterized primarily by a much shorter time and lower energy consumption compared to conventional extraction methods [39].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of ultrasound-assisted extraction are based on fragmentation, erosion, sonoporation, and detexturation [38]. The mass transfer to the liquid phase is improved due to the collapse of cavitation bubbles, and moreover, this process is characterized primarily by a much shorter time and lower energy consumption compared to conventional extraction methods [39].…”
Section: Discussionmentioning
confidence: 99%
“…The objective of that research was to determine optimum conditions for oil extraction. The outcomes showed that optimal conditions were amplitude (95 %) and extraction time (11.38 min), which resulted in maximum extraction yields (22.55 ± 0.36 %) [138] . Hence, it has been proved that the UAE is an effective technology for recovering and enhancing essential oil from fruits and vegetable seeds.…”
Section: Recovery Of Biomolecules From Food Wastementioning
confidence: 99%